New Product Development With A Customer-Centric Approach to Meet Dynamic Market Needs - Dony Ari Nugroho (Eduvest - Journal of Universal Studies, 2025)
This research explores the application of a customer-centric approach in new product development to meet the needs of a dynamic market. Using qualitative methods, including in-depth interviews, focus group discussions (FGDs), and analysis of company documentation, this study identifies the best strategies, challenges, and impacts of implementing this approach on product success. The results show that the integration of customer feedback and the effective use of analytical data can improve customer satisfaction and product sales performance. However, companies face challenges in terms of resource constraints, internal resistance, and consumer data collection. The study recommends companies to allocate adequate resources, involve teams in decision-making, and use advanced technology for data optimization. For further research, it is recommended that the focus be on applying a customer-centric approach across various industries and company scales, as well as solutions to overcome specific obstacles faced.